Peran Rumah Makan Citra Minang Terhadap Penyerapan Tenaga Kerja - Romauli Situmorang; Cahya Putri Ramandhani; Asima Pasaribu; Ema Serika Ginting; Mira Susilawarni; Agnes Rebeca Sianturi (Pusat Riset dan Inovasi Nasional, 2024)
Rumah Makan Citra Minang was established in 2020 and has become one of the favorite places to eat in Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. However, in recent times the Citra Minang Restaurant has experienced several obstacles that can hinder the progress of its business and labor productivity. The purpose of this study is to find out how the influence of citra minang restaurants on labor absorption. And this data was collected through direct observation to the research site using quantitative and qualitative data analysis techniques. The results of this study show that the Citra Minang restaurant has a very significant role in the absorption of labor as well as the local economy and the wider community.